2012
DOI: 10.1016/j.jsv.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acoustic networks including cavities by means of a linear finite volume method

Abstract: A procedure allowing for the analysis of complex acoustic networks, including three-dimensional cavities described in terms of zero-dimensional equivalent elements, is presented and validated. The procedure is based on the linearization of the finite volume method often used in gas-dynamics, which is translated into an acoustic network comprising multi-ports accounting for mass exchanges between the finite volumes, and equivalent 2-ports describing momentum exchange across the volume surfaces. The application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…11, both for the transmitted pulses in the time domain and the resulting transmission loss in the frequency domain. In this last case, the transmission loss computed with the linear frequency-domain counterpart of the present method, which was described and validated in reference [34], is also included as a reference. In the time domain representation, it can be observed that the results of the original method are severely affected by spurious oscillations that extend along the whole decay of the pulse.…”
Section: Application To a Simple Geometrymentioning
confidence: 99%
“…11, both for the transmitted pulses in the time domain and the resulting transmission loss in the frequency domain. In this last case, the transmission loss computed with the linear frequency-domain counterpart of the present method, which was described and validated in reference [34], is also included as a reference. In the time domain representation, it can be observed that the results of the original method are severely affected by spurious oscillations that extend along the whole decay of the pulse.…”
Section: Application To a Simple Geometrymentioning
confidence: 99%
“…First, an extension to absorbent materials of the linear finite volume method described in [12] and [13] was developed for the case in which, as expected, the material would behave as a bulk-reacting liner. Secondly, a transfer matrix model assuming a locally-reacting liner [14] was implemented, as the lack of information in the actual behavior of these novel materials does not permit to establish in advance which is the actual attenuation mechanism implied.…”
Section: Modelsmentioning
confidence: 99%
“…In the frame of the finite volume calculation described in [13], a given region is regarded as built of smaller volumes, and a staggered mesh system is used, i.e. a one-dimensional momentum equation is solved at the interfaces between volumes.…”
Section: Model With Bulk-reacting Materialsmentioning
confidence: 99%
“…5 The wide application of some commercial code in design further promotes the development of FEM and BEM. Up to now, FVM in this field is still a quite new topic and rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, FVM in this field is still a quite new topic and rarely reported. Torregrosa et al 5 successfully employed the frequency domain FVM to analyze three-dimensional (3D) complex acoustic networks in the absence of a mean flow and the results were validated by experimental or computational data. Their work provides a new alternative tool for predicting acoustic performance of mufflers.…”
Section: Introductionmentioning
confidence: 99%